O-02 Complex, provocative, humbling and enlightening – equality, diversity and inclusion. (19th November 2022) - Clarke, Karen
Abstract : Background: An equality, diversity and inclusion (EDI) audit was commissioned to assess whether hospice stakeholders felt included, with their needs met and their contributions valued, and to ensure that unintentional bias had not crept in. Aim(s): Assess policies, processes and EDI interventions' effectiveness. Understand EDI perceptions and aspirations, and stakeholders' 'lived experience'. Strategically address gaps identified. Methods: Policies, processes, equality monitoring data and external profile were reviewed, and questionnaires, listening groups and individual interviews were conducted with a range of stakeholders. Findings: Despite evidence of senior level commitment to improve, and pockets of significant EDI interest, knowledge and expertise, there was a lack of: A strategic EDI focus and the hospice was 'behind the curve'. Diversity in: employee and volunteer profiles and therefore understanding of different lived experiences the physical hospice environment, sending an inaccurate message to the community about the hospice's ethos and approach inclusivity in hospice branding, meaning some local minority communities felt the hospice was 'not for them'. There was an organisational EDI blind spot where unconscious bias played out in unintentionally exclusionary behaviours affecting culture and impeding inclusive service delivery. Progress: 'Proud to be' series, sharing lived experiences, launched. EDI Lead appointed, and governance framework implemented. EDI objectives agreed. Mandatory Conscious Inclusion training. Partnership working with local community. Regional EDI forum established. How innovative or of interest is the abstract?: EDI is complex and provocative, requiring humility and a willingness to learn. It requires courage to hold firm in the face of criticism by those whose own views of hospice may be challenged. The 'Proud to be' series and training has created the psychological safety for colleagues to share lived experiences without fear of judgment or adverse treatment. This has allowed the entire organisation to grow.